Optimalization of Bioconversion Prosess of Palm Kernel Cake For Production Maggot Hermetia Illucens as A Source of Animal Protein in Fish Farming - Bokau, Rietje J.M; Witoko, Pindo (Indonesian Aquaculture Society (MAI), 2017)
The process of bioconversion of palm kernel cake (PCK) for the production of Black Soldier Fry larva biomass as a fish feed can be improved by fermentation process. The purpose of this research was to determine the amount of biomass production and nutritional content of maggot as a result of bioconversion fermented palm kernel cake (PCK) by using probiotic. PCK used in this research were obtained from one of palm processing industry (PTP VII Lampung). Fermentation process was using microbes (probiotics) amount of 0% (F0), 3% (F3), 4% (F4), and 5% (F5) in 1 liter of water, then it's mixed with PKC to help fermentation process. Each treatment was using 3 replication. The fermentation process was done in a 3 liters volume of bucket covered by perforated black plastic/trash bag to avoid the heat by light and the rainwater. The buckets were prepared, placed and stored in a cool and humid place by using a bamboo/wooden racks. If the media was prepared, Black Soldier Fly (BSF) insect would automatically come and lay its eggs on it.. Observations were made within 2 weeks after the media were prepared and then harvested 3 times during one week. The biomass of harvested maggot were clasified into 3 group of size, they are <1cm, 1-1.5cm, and >1.5cm, then the weight were measured. The result showed that the fermented media did not give any affect for the biomass of maggot, but had an effect on the maggot nutrition. The biomass of maggot in the treatment F0 (control) was not significantly different from treatment F3 (3%) (p>0.05), while the higher dose of probiotic (F4 and F5) were lower than control. The proximate composition of maggot showed that crude protein and fat parameter were significantly different for every stage of fermentation treatment. Treatment F3 has the highest crude protein and significantly different from F0 and F5 (p<0.05), while the fat contents decreasing significantly at higher fermentation dose. Likewise, the total amino acid, in fermentation F3 was significantly higher compared to control and other treatments. Thus, the dose of fermentation (probiotic in water) 3% for the PKC was optimal to produce biomass and nutritional content of maggot.